Fundamentals of vibration analysis - Myklestad, Nils O. (Dover books on engineering., 2018)
This concise textbook discusses vibration problems in engineering, dealing with systems of one and more than one degrees of freedom. A substantial section of Answers to Problems is included. 1956 edition.